STRATEGIES FOR ACHIEVING OPEN DEFECATION FREE (ODF) VILLAGES IN BALI PROVINCE - Ni Made, Kasturiani; Ni Putu, Pandawani; I Made, Wahyu Wijaya (Babali Publisher, 2026)
Background: The availability of safe and adequate sanitation can reduce high infant and under-five mortality rates. Access to sanitation in Bali Province reached 97.12% in 2021; however, the achievement of Open Defecation Free (ODF) villages remained very low at only 45.5%, below the national average of 48.7%. Even by the second quarter of 2022, out of 716 villages/ward, only 330 (46.09%) had achieved ODF status. Accordingly, this study was conducted to determine strategies for achieving ODF villages in Bali Province. Method: The study used a cross-sectional design. It was exploratory in nature, examining internal and external conditions in the form of strengths and weaknesses (internal factors) as well as opportunities and threats (external factors). These strategic factors were analyzed using a SWOT model. Results: The presence of rewards/incentives for ODF villages and an STBM monitoring system were showed significant strengths (score 0.63). The main weakness factor was the lack of cross-sectoral coordination (score 0.52). The highest-scoring opportunity factor was the triggering of behavior change and health promotion by community health centers (Puskesmas) (score 0.67), while the most significant threat factor was the limited availability of clean water facilities (score 0.73). Conclusion: Strategies for achieving ODF villages include: strengthening programs through regulations, budget allocation, monitoring-evaluation systems, cross-sectoral collaboration, sanitation technology development, capacity building of potential human resources, integration of STBM with other priority programs, one of which is the Settlement Sanitation Development Program. Keywords: Open Defecation Village, Bali Province, SWOT Model